Empowerment of Agroindustry Groups in An Effort to Accelerate East Java's Economic Growth - Astutiningsih, Sri Eka; Sari, Citra Mulya (Jurnal Ilmu Ekonomi Terapan, 2017)
The majority of the Indonesian population, especially in East Java live in rural areas, and most are farmers. Then to the economic development of rural farmers as a unity between the agricultural sector and small industrial group aimed at empowering agroindustry. Agroindustry is the best answer, since it relates to the rear (backward linkage) and the linkage to the front (forward linkage) long. Empowerment of agroindustry in itself is not easy, a lot of problems to deal with, among others: (1) the ability of the technology used is not optimal, (2) the quality of human resources (HR), (3) coordination and synchronization institutional program, (4) creation of business climate conducive. The government has implemented fiscal policy to encourage the use of small industrial products in order to export, encouraging the growth of business-incubation as well as the development of "ancillary industries ‘' through tax relief, monetary policy to support the financing of capital investments and working capital through credit schemes specifically tailor our flexible, development financial institutions, administrative and real for the simplification of licensing procedures and investment, import-export procedures, joint development with major industry in the country and abroad, the implementation of the Small Business Act, especially in managing the trade patterns and the pattern of payments through the backup market. If these four indicators are met and determined government policy will spur the growth of the local economy, so it could eventually resolve the problems in the village.